Tunable broadband photoluminescence from bismuth-doped calcium aluminum germanate glasses prepared in oxidizing atmosphere - Cao, Jiangkun; Ding, Yicong; Limbach, Rene; Nozari, Vahid; Sajzew, Roman; Sun, Minghui; Zhang, Pengzhu; Wondraczek, Lothar (Journal of the American Ceramic Society, 2022)
Tunable photoluminescence (PL) from transparent inorganic glass matrices is of interest for applications demanding a semitransparent photoconverter that does not elastically scatter incoming light. For this purpose, bismuth (Bi)-doped optical materials exhibit unique spectral characteristics in terms of bandwidth and emission tunability. Here, we demonstrate a facile route for preparing such converters from Bi-doped calcium-aluminate and calcium-aluminogermanate glasses. These glasses offer tunable PL across the near violet and visible-to-near-infrared (NIR) spectral range, with an emission lifetime in the range of 300 μs. The addition of GeO2 exerts a decrease in optical basicity, which in turn enables the stabilization of NIR-active low-valence Bi species for broadband NIR PL.
CRIS-Team Scopus Importer:2023-04-20
Keywords: bismuth; broadband; glass; NIR; photoluminescence